Mouse strain differences determine severity of iron accumulation in Hfe knockout model of hereditary hemochromatosis - Fleming, Robert E. (The National Academy of Sciences, 2001)
Hereditary hemochromatosis (HH) is a common disorder of iron metabolism caused by mutation in HFE, a gene encoding an MHC class I-like protein. Clinical studies demonstrate that the severity of iron loading is highly variable among individuals with identical HFE genotypes. To determine whether genetic factors other than Hfe genotype influence the severity of iron loading in the murine model of HH, we bred the disrupted murine Hfe allele onto three different genetically defined mouse strains (AKR, C57BL/6, and C3H), which differ in basal iron status and sensitivity to dietary iron loading. Serum transferrin saturations (percent saturation of serum transferrin with iron), hepatic and splenic iron concentrations, and hepatocellular iron distribution patterns were compared for wild-type (Hfe +/+), heterozygote (Hfe +/−), and knockout (Hfe −/−) mice from each strain. Although the Hfe −/− mice from all three strains demonstrated increased transferrin saturations and liver iron concentrations compared with Hfe +/+ mice, strain differences in severity of iron accumulation were striking. Targeted disruption of the Hfe gene led to hepatic iron levels in Hfe −/− AKR mice that were 2.5 or 3.6 times higher than those of Hfe −/− C3H or Hfe −/− C57BL/6 mice, respectively. The Hfe −/− mice also demonstrated strain-dependent differences in transferrin saturation, with the highest values in AKR mice and the lowest values in C3H mice. These observations demonstrate that heritable factors markedly influence iron homeostasis in response to Hfe disruption. Analysis of mice from crosses between C57BL/6 and AKR mice should allow the mapping and subsequent identification of genes modifying the severity of iron loading in this murine model of HH.